Mechanism of injury and disposition of severe polytrauma patients at Kalafong Hospital 2018/2019 - Onke P. Tuswa; Maria M. Geyser; Vidya Lalloo; Almien Smit (Journal of the Colleges of Medicine of South Africa)
Background: The most common mechanisms of injury (MOI) for trauma patients in South Africa (SA) are transport-related and interpersonal violence. South Africa is rated among the highest in the world with regard to mortality from injuries sustained, yet many tertiary public hospitals do not have dedicated trauma teams. The aim of this study was to observe the MOI and disposition of severe polytrauma patients presenting to Kalafong Provincial Tertiary Hospital (KPTH) emergency department (ED). A secondary aim was to observe associations between the MOI, severity of injuries, and patient outcome.